Rhetorical Styles in Janji Jiwa’s Instagram Captions During the Transition of 2020 COVID-19 Pandemic - Claudia Veriona (Institute of Research and Community Outreach - Petra Christian University, 2022)
I undertook this study to present an analysis of the rhetorical styles utilized by Janji Jiwa in writing their Instagram captions and the similarities and differences between the two forms of rhetorical language during the transition period. The language style theory by Keraf (2006) serves as the foundation for this study. I employed a qualitative approach in this research. The findings of the study revealed that Janji Jiwa used rhetorical styles in most of their captions, employing a total of nine distinct rhetorical styles. The comparison was not significant because the company was still in the process of transitioning to the pandemic. In conclusion, Janji Jiwa is considered to have had a good start in dealing with the pandemic transition situation and is still trying to continue to adapt to it. Future research is expected to do the research on the same thing, but in other industries.